An efficient algorithm for unique class association rule mining. (February 2021) - Nasr, Mahmoud; Hamdy, Mohamed; Hegazy, Doaa; Bahnasy, Khaled
Highlights: Unique patterns extraction of datasets. Efficient and complete search for Class-based association rules CARs. Performance of extracting CARs based on the Subsumption and Nonsense hypotheses. Building rule-spaces and Ranking of datasets. Abstract: Association rule mining is one of the main means in Knowledge discovery and Machine learning. Such kind of rules present knowledge of interrelations among items in a dataset. Class Association Rules (CARs) are a subset of association rules which are always mined using labeled datasets. Simply, a typical CAR has an itemset that is associated to a class label. Mining CARs is vital for construction of pattern or rule-based classification models and has received recently increasing research interest. In this work, a complete efficient but not exhaustive CAR mining algorithm (UniqAR) is introduced. UniqAR generates always and only 100 % accurate CARs which are called unique association rules using two rule search hypothesis of Subsumption and Nonsense to find unique itemsets in order to generate the Unique CARs. Unlike alternatives of CAR mining algorithms, UniqAR mined association rules aren't based on itemset frequency or item selectivity. It can generate both frequent and rare association rules. No preferences of support, coverage, or item participant in itemsets are required to be provided for the proposed mining process. The main contribution of this work to CARs' state of the art is describing unique itemsets and class association rules and providing an efficient mining process for them. Unlike the other unique rule mining alternatives in the literature, the proposed novel mining process depends on a complete but not exhaustive search that employs rules inter-relations. UniqAR has been modeled with computational analysis and extended evaluation. It is shown that UniqAR can extract all unique itemsets for unique association mining with no need to setup any user preferences, template or any constraints. Moreover, it describes accurately the effects of different dataset criteria like number of attributes/features, feature values, cases, and class labels on UniqAR unique itemset extraction mining process in an efficient way that avoids a huge number of itemsets/cases comparisons. Results have shown that the proposed UniqAR algorithm is feasible and promising.